Null subject and null object in child Chinese. - Wu, Bin. (University of Ottawa (Canada), 2000)
This study is focused on the null subject and object phenomenon in Chinese child language. Its goal is to investigate null subject and object use in the Chinese spontaneous speech in the light of the debates in the previous literature. The first two chapters elaborate on the adult grammar of the empty categories and the debates about this phenomenon in the Chinese linguistic literature. Two types of approaches are introduced in these two chapters. A detailed account of the data analysis regarding the Chinese children's naturalistic speech is given in Chapter Four, in comparison with Valian's (1991, 1995) work on child English, Italian and Portuguese. The basic finding of this study is that Chinese speaking children increase their use of subjects, particularly their use of pronominal subjects, as they get older. This strongly demonstrates that this study has accomplished its goal of supporting the performance-based accounts of children's subject and object use.
Keywords: Language, Linguistics.